Orca (Orcinus orca) and shark predator-prey interactions within Cabo Pulmo National Park in the Gulf of California, Mexico - Ayres, Kathryn A.; Gallagher, Austin J.; Higuera-Rivas, Jesús Erick (Frontiers in Marine Science, 2024)
Orcas (Orcinus orca) have a worldwide distribution and as apex predators feed on a wide variety of prey, including marine mammals, seabirds, sea turtles, cephalopods, teleost fish and elasmobranchs. Historically, there have been few observations of orca predation on large elasmobranch species nor are they commonly identified in the stomach contents of deceased orcas. In recent years there has been an increase in observational records of orca predation, such as on white sharks (Carcharodon carcharias) in South Africa, which could indicate that elasmobranchs serve a greater importance in their diet than previously considered. These events are often documented by members of the public due to the development and affordability of innovative cameras, including the use of the drones (unoccupied aerial vehicles). Here we describe new predator-prey interactions between orcas and large shark species in Cabo Pulmo National Park (CPNP), a small no-take marine protected area located in the Gulf of California. In this paper, we were able to successfully identify individuals from the described orca pods in the region; specifically, the same individuals hunting sharks over a period of nearly two years. We discuss the potential implications of these new ecological interactions, given the importance of tourism to sustain the management of CPNP, as cascading impacts have been documented elsewhere in light of orca predations on sharks.